Hepatitis B Virus in Polish Blood Donors in the Period 2005–2019—Significant Changes in Epidemiology and Demographic Characteristics of Infected Donors - Kopacz, Aneta; Kubicka-Russel, Dorota; Liszewski, Grzegorz; Sulkowska, Ewa; Chrzanowska, Anna; Zwolińska, Paulina; Noceń, Ewa; Potępa, Anna; Łętowska, Magdalena; Grabarczyk, Piotr (Viruses, 2025)
In the 1980s, Poland was a medium-endemic country, with one of the highest incidences of hepatitis B in Europe (45/105 inhabitants). Pursuant to the WHO guidelines, obligatory vaccination was introduced in 1994–1996 (as a part of hepatitis B prophylaxis for newborns), and in 2000–2011, all 14-year-olds were vaccinated. To prevent transfusion-transmitted HBV infection (TT-HBV), since the 1970s, each donation has been tested for HBsAg and, since 2005, additionally for the presence of HBV DNA. Based on the data from the Blood Transfusion Centers, changes in HBV detection in Polish blood donors were analyzed, starting from the introduction of mandatory NAT screening until 2019. During the period under analysis, a total of 11,625 HBV-infected donors were identified: 97.95% were seropositive (confirmed HBsAg) and 2.05% were seronegative (NAT yields). The detection frequency for both categories of infections was significantly (p = 0.05) higher for men than for women (Residual Risk RR = 1.4 and RR = 2.63, respectively). Seropositive infections were detected more frequently (p < 0.05) in first-time donors than in repeat donors (RR = 360), while no significant differences were observed in the category of seronegative infections. A downward trend in HBsAg detection was observed in both first-time and repeat donors (Spearman’s coefficient R = −0.98 and R = −0.90, respectively). The frequency of HBsAg in first-time donors decreased 5-fold, and, in repeat donors, 30-fold. In both subpopulations, the largest decrease occurred in the age group ≤ 20 years (i.e., donors born between 1985 and 2001). The incidence of window period (WP) infections in the repeat donor group demonstrated a downward trend (R = −0.54, p < 0.05), and in the first-time donor group, no significant trend was recorded. For occult hepatitis B infection (OBI), no significant trend was observed in either donor subpopulation. WP infections were detected significantly more often in donors aged 21–50 years than in donors ≤20 years, most often in the 41–50 age group. The frequency of OBI increased with donor age and was the highest in the 51–60 age group. A spectacular decrease in the frequency of HBsAg(+) infections was observed in current study, indicating the effectiveness of the hepatitis prevention strategy applied in Poland. We expect that the improvement in the epidemiological situation among blood donors causes a reduction in the risk of TT-HBV. Confirmation of this hypothesis by the analysis of residual risk should be a subject of further studies.